Judicial Order Sebagai Penguatan Sifat Final Dan Mengikat Putusan Mahkamah Konstitusi Dalam Perkara Pengujian Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum - Mutiara Miyonita; Arfiani; Feri Amsari (Lareh Law Review, 2024)
The authority of the Constitutional Court in the judicial review against the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) is stated in Article 24C paragraph (3). One of the most frequently proposed judicial review is Law Number 7 of 2017 about General Elections (Election Law). The result of this review is the Constitutional Court's decision which is final, so no other legal action can be taken after the decision is issued. However, in reality the Constitutional Court's decision regarding the Judicial review of Election Laws experienced various problems in its execution which were referred to as constitutional disobedience . In other countries such as Germany, the Federal Constitutional Court uses the concept of judicial order to resolve this problem. The judicial order is an important message for the future Legislature to implement the Constitutional Court's decision through concrete follow-up. Formulation of the problem raised in this research First, what is the urgency of using a judicial order in the Constitutional Court Decision in the Election Law judicial Review? Second, what are the differences in the implementation of Constitutional Court Decisions containing judicial orders in judicial reviewing of the Election Law? The type of research used is normative juridical. Data collection techniques use library research. Data will be analyzed using qualitative analytical descriptive methods. The research results explain that in order to realize legal certainty in order to carry out direct, public, free, secret, honest and fair elections, this Constitutional Court Decision needs to be implemented immediately. For that reason, judicial orders that have been implemented by the Indonesian Constitutional Court and other countries prove its function in strengthening the final and binding effect of its decisions. Differences in the implementation of Constitutional Court decisions that contain judicial orders can be seen in several non-self-executing decisions, there are decisions that are fully implemented, partially implemented, not implemented and also implemented differently from orders from Constitutional Court decisions